Analysis on Subsidence Law of Bedrock and Ultrathick Loose Layer Caused by Coal Mining. (6th August 2021) - Shi, Weiping; Li, Kaixin; Yu, Shengwen; Zhang, Cunzhi; Li, Jingkai
Abstract : In the process of coal mining, when the buried depth is large and the loose layer is thick, the ground subsidence tends to be abnormal, thus causing great damage to the surface ecological environment. In order to reveal the mechanism of mining ground subsidence under ultrathick loose layer, taking 1305 working face of a mine as the background, the law of mining ground subsidence under ultrathick loose layer was analyzed through field measurement. The law of bedrock subsidence is analyzed by similar simulation test, and the role of ultrathick loose layer in bedrock subsidence is quantitatively analyzed. The hydrophobic settlement model of ultrathick loose layer is established by settlement theory calculation, and the law of ground subsidence caused by hydrophobic of ultrathick loose layer is analyzed. The results show that the ground subsidence is mainly composed of bedrock subsidence and hydrophobic settlement of ultrathick loose layer. The maximum ground subsidence measured in the field is 4.201 m, the bedrock surface subsidence obtained by the simulation test of similar materials is 3.552 m, and the subsidence of ultrathick loose layer obtained by hydrophobic settlement analysis is 0.58 m. Adding the subsidence of bedrock surface and the subsidence of ultrathick loose layer, the ground subsidence is 4.132 m. It is in good agreement with the total ground subsidence measured in the field, which verifies the rationality that the ground subsidence mainly includes bedrock subsidence and hydrophobic settlement of ultrathick loose layer.